A public health policy approach to reducing economic and health costs of obesity in the USA. (23rd February 2015) - Pasupathy, Rubini; Coppola, M. Nicholas; Posteraro, Robert
Obesity is rapidly increasing in the USA. It is one of the most serious public health problems that significantly increase the risk of many chronic illnesses. Obesity disproportionately affects people with lower incomes and minority groups and imposes a heavy financial burden on the healthcare system in the USA. Thus, there is a critical need for healthcare policies that are designed to stem the growth of obesity. The aims of this paper are to discuss the cost of obesity to the national healthcare expenditure, and to present and discuss various policies and strategies adopted by several states across the country to prevent the growth of obesity. Additionally, the role of interest groups and political will with respect to formulating healthcare policies on preventing obesity are discussed. A multifaceted approach that incorporates market and cultural forces is recommended to prevent obesity and reduce healthcare costs.